2002
DOI: 10.1161/hc0202.102119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Myocardial Blood Flow Impairment in Idiopathic Left Ventricular Dysfunction

Abstract: Background-Depressed myocardial blood flow (MBF) has been reported in dilated cardiomyopathy. The aim of this study was to investigate whether MBF impairment is an independent predictor of prognosis in patients with idiopathic left ventricular (LV) dysfunction. Methods and Results-Sixty-seven patients (52 male, mean age 52Ϯ12 years) with different degrees of idiopathic LV systolic dysfunction (average LV ejection fraction, 0.34Ϯ0.10; range, 0.07 to 0.49) were prospectively enrolled. Thirty-four subjects (51%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
234
3
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(268 citation statements)
references
References 31 publications
16
234
3
9
Order By: Relevance
“…This is not surprising as in patients with hypertrophic or dilated cardiomyopathy (and no epicardial coronary artery disease),20, 21 stress MBF has been shown to be superior to perfusion reserve for uncovering coronary microvascular dysfunction and predicting adverse cardiac events 22…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as in patients with hypertrophic or dilated cardiomyopathy (and no epicardial coronary artery disease),20, 21 stress MBF has been shown to be superior to perfusion reserve for uncovering coronary microvascular dysfunction and predicting adverse cardiac events 22…”
Section: Discussionmentioning
confidence: 99%
“…Tissue ischemia occurs within the myocardium in DCM, possibly due to a decreased supply caused by microvascular structural and functional abnormalities. Indeed, recent studies have shown that the reduction in myocardial blood flow and volume have been observed in patients with DCM [29,30]. Therefore, it is very likely that the increased serum activity of VEGF in patients with DCM is involved in myocardial perfusion abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…CV-IB can be of value in quantifying regional differences in myocardial contractile performance in DCM. Moreover, it is known that the reduction in myocardial blood flow influences attenuation and scattering of myocardial tissue, and could be associated with the deterioration of LV systolic function [29,30]. Accordingly, the increase in serum VEGF may be closely associated with the impaired intrinsic myocardial contractile performance caused by myocardial microvascular abnormalities and myocardial interstitial fibrosis in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…The development of impaired coronary reserve has been well recognized in patients with idiopathic dilated cardiomyopathy and implies a poorer prognosis in the long term. 32 In HTN, microvessel disease might be a marker of concurrent idiopathic dilated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%